Metacognitive Conceptual Change (MCC) Learning Model: Improving Students' Conceptual Change through Metacognitive Skills, Motivation, and Scientific Knowledge - Syahmani, S.; Hafizah, E.; Sholahuddin, A.; Sauqina, S.; Prasetyo, Y. D.; Rahman, N. F. A. (Jurnal Pendidikan IPA Indonesia, 2023)
Conceptual change (CC) is a learning process in which students’ misconceptions are transformed into more scientific knowledge. The Metacognitive Conceptual Change (MCC) learning model is created by incorporating metacognitive skills and motivation elements into the CC model to make it more effective. It is necessary to look into the MCC model’s efficacy in encouraging students’ CC. This study aims to evaluate the MCC model’s effectiveness in improving conceptual changes in students through metacognitive skills, motivation, and scientific knowledge. This study used the experimental method with a one-group pretest-posttest design. The trial subjects were limited to 25 participants, while the broad trial subjects comprised 60 participants. Data was collected from tests, observations, questionnaires, and documentation. Data analysis techniques used in this study were descriptive, qualitative (n-gain test), and quantitative (paired t-test). The results demonstrate that the MCC learning model successfully raises students’ motivation, scientific knowledge, and metacognitive skills (p Sig. 0.05), encouraging the CC process. It is concluded that the MCC learning model effectively improves students’ CC by incorporating scientific knowledge, motivation, and metacognitive skills into instructional decisions. The MCC has practical implications for assessing CC through motivation and metacognitive scaffolding.